ANALYSIS OF FLOOD DISASTER VULNERABILITY LEVELS IN RAMBAH DISTRICT OF ROKAN HULU REGENCY - Widya Septianingsih; Paus Iskarni (JURUSAN GEOGRAFI FIS UNP, 2022)
This research aims to 1) know the distribution of floods in Rambah Subdistrict. 2) know the Level of Flood Insecurity 3) know the linkage of existing landuse to flood-prone areas. The data analysis techniques used are score and weighting with the paimin method using ArcGIS 10.4. Research Results 1) Flood distribution in Rambah has 3 classes prone to flooding, low class 73.78% moderate class 19.15% high prone class 7.06% 2) Flood vulnerable Level based on Rainfall, Slope, Height, Soil Texture, Soil Permeability, Land Use, River is obtained the results of classification of 3 classes, not prone 11976,03 Ha, vulnerable class 21071,53 Ha and very vulnerable class 1407,78 Ha. 3) The relation of land use with flood vulnerable is not prone, namely forests 4581.79 Ha and the lowest settlement is 0.55 Ha. Plantations for vulnerable class 10224.48 Ha class is very prone to plantations 670.62 Ha, flood settlements are very prone 147.53 Ha.